THE USE OF MODERN CASE-TOOLS OF STRUCTURAL DESIGN IN TEACHING STUDENTS ON THE BACHELOR PROGRAM “APPLIED INFORMATICS” - Alexander V. Gavrilov (Открытое образование (Москва))
Introduction in educational process of CASE-technologies requires a significant investment of the institution for the purchase of software. A possible solution is to use free software peers. This article provides an overview of the CASE-tools free structural design, methods of selection of CASE-tools for use in the educational process.